2019
DOI: 10.1002/ijc.32637
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of weight loss in primary breast cancer: Impact on body composition, circulating biomarkers and tumor characteristics

Abstract: Obesity adversely impacts overall and cancer‐specific survival among breast cancer patients. Preclinical studies demonstrate negative energy balance inhibits cancer progression; however, feasibility and effects in patients are unknown. A two‐arm, single‐blinded, randomized controlled weight‐loss trial was undertaken presurgery among 32 overweight/obese, Stage 0–II breast cancer patients. The attention control arm (AC) received basic nutritional counseling and upper‐body progressive resistance training whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The remaining five studies applied the weight loss interventions post-cancer treatment and only blood samples were analyzed. When comparing the serum cytokine levels in the weight loss intervention group to the control, TNFα (145,147,148), IL-6 (145,(147)(148)(149), and CRP (148,149) were mainly unchanged. When comparing post-intervention to preintervention, TNFα (146) and CRP (144) were unchanged in one study, while IL-6 was reduced in one study (146).…”
Section: Clinical Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…The remaining five studies applied the weight loss interventions post-cancer treatment and only blood samples were analyzed. When comparing the serum cytokine levels in the weight loss intervention group to the control, TNFα (145,147,148), IL-6 (145,(147)(148)(149), and CRP (148,149) were mainly unchanged. When comparing post-intervention to preintervention, TNFα (146) and CRP (144) were unchanged in one study, while IL-6 was reduced in one study (146).…”
Section: Clinical Findingsmentioning
confidence: 97%
“…All six studies were conducted in cancer patients with overweight or obesity, and weight loss interventions included the combination of PA and ER. Five out of the six studies (144)(145)(146)(147)(148) were conducted in breast cancer patients, and one study (149) recruited patients of a mix of cancer types. One study (145) assessed the effect of a pre-surgical weight loss intervention on serum and intratumoral immune and inflammatory markers.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Evidence in support comes from randomized and controlled trials implementing behavioral or lifestyle interventions to bring about changes to physiology. For example, one study randomized 32 overweight or obese stage 0-II breast cancer patients into an intervention and control group as part of a 30 day pre-surgery “weight loss” study ( 320 ). The intervention group received counseling on caloric restriction and aerobic exercise to promote a change in body mass of 0.68–0.92 kg/week.…”
Section: The Relevance Of Aging and Lifestyle For Cancer Biomarker Prmentioning
confidence: 99%
“…CR-mediated reduction in cancer cell proliferation is central to anti-cancer animal model studies. The clinical trial studies showed no negative energy/calorie restriction effects on cell proliferation marker Ki-67 in Barrett's esophagus [13] and breast cancers [14]. In men with prostate cancer, presurgical weight loss showed CR-mediated Ki-67 upregulation [12].…”
Section: Introductionmentioning
confidence: 98%
“…Recent randomized clinical trials have been explored for potential CR anti-cancer properties [12][13][14]. These trials showed mixture effects of CR directly on tumor tissue growth, host immune cells response, and other tissue responses (e.g., adipocytes).…”
Section: Introductionmentioning
confidence: 99%